EVALUATION OF ANTICANCER POTENTIAL OF EIGHT VEGETAL SPECIES FROM THE STATE OF OAXACA - Lira-De León, Karla Isabel; Herrera-Martínez, Mayra; Ramirez-Mares, Marco Vinicio; Hernández-Carlo, Beatriz (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Eight plant species from Oaxaca, some of them used in traditional medicine, were subjected to screeningof several biological activities to provide data regarding their anticancer potential, although no scientific information isavailable about their pharmacological effects.Materials and methods: Methanol extracts from stems or roots of the eight plants were tested for antioxidant activityby the DPPH· method. Antimicrobial activity was determined using the agar diffusion method and the minimalinhibitory concentration (MIC) was obtained by broth dilution method. Antitopoisomerase activity was assessed usingmutant strains of Saccharomyces cerevisiae JN362a, JN394, JN394t-1, JN394t2-4 and JN394t2-5. The mutagenic activitywas evaluated using the Ames test (Salmonella typhimurium TA1535).Results: No extract showed significant antioxidant activity. The best antimicrobial activity was observed forSalpianthus arenarius (MIC 56.25 μg/mL) and Lantana achyranthifolia (MIC 78.12 μg/mL) against Staphylococcusaureus. Extracts of Acalypha cuspidata, Alloispermum integrifolium and L. achyranthifolia stems showedantitopoisomerase II activity with JN394t-1 growth of -30.88±0.0%, -38.11±4.95%, and -70.97±12.02% respectively.Galium mexicanum stem extract showed antitopoisomerase I activity with growth of 35.31±6.36% on the same mutantstrain. All plant extracts were non-mutagenic. Fractionation of A. cuspidata extract led to identification of twosubfractions with antitopoisomerase I and II activity at 154μg/mL (Positive controls 50 and 100μg/mL).Conclusion: Methanol extracts of A. cuspidata, A. integrifolium, G. mexicanum, and L. achyranthifolia stems showedantitopoisomerase and non-mutagenic activities, and consequently could be promising as a source of anticancer drugs.